Achieving broadband RCS reduction using carbon fiber connected composite via scattering mechanism. (10th November 2020) - Yang, Jiaheng; Pang, Yongqiang; Wang, Jiafu; Sui, Sai; Jiang, Wei; Zhang, Jieqiu; Qu, Shaobo
Abstract: In this paper, a skillful structure composed of the glass fabric composite and patterned carbon fiber (CF) yarns is proposed, which achieves the goal of RCS reduction over a wide frequency band. The reduction mechanism is the scattering instead of traditional absorption. Two constitutive regions providing suitable phase difference are continuously connected with full fiber yarns by needle punching method. Both calculation and simulation analytically reveal that how to work for beam-redirecting in our design. Carrying out the specular reflectivity test, it is demonstrated that our proposal exhibits a remarkable capability of reflection suppression, whose 10-dB level RCS reduction band is achieved from 8.0 GHz to 24.1 GHz. Moreover, the anisotropic regions in chessboard pattern makes the proposed structure independent of different polarizing conditions. It is sure that our proposal possesses the advantages of simple unit structure and easy fabrication, which has more practical values in the application of radar stealth design. Graphical abstract: Image 1